Studi Deskriptif Pembuatan Karya Montase Tema Lingkungan Sehat Kelas IV SD Negeri 5 Kota Bengkulu - Rahmadani, Yemi; Tarmizi, Pebrian (JURIDIKDAS, 2026)
This research aims to describe the process of making montage art works and the results of montage art works for class IV Elementary School 5, Bengkulu City. The type of research used in this research is descriptive qualitative research. The subjects of this research were 3.0 students in class IV of Bengkulu City State Elementary School 5. Data collection techniques were in the form of observation sheets, interviews and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the research are (1) the process of making a montage work on the theme of a healthy environment, consisting of 5 groups based on indicators of a The stage of making a montage work is the preparation stage, each group prepares tools and materials In the second stage of initial arrangement (temporary arrangement), groups 4 and 5 felt confused when arranging the image pieces, after that the permanent arrangement stage, each group attached the image pieces on the base area with using glue. The final finishing stages for groups 1 and 4 are adding colored strokes around the image. (2) the results of the montage work on the theme of a healthy environment seen from the indicators channels which consists of 5 montage works, in the work of group 1 there are no pictures of people throwing rubbish in their places, only pictures of places. Concluded that each group has been created through preparation stages, initial structuring stages and final completion.